Instrumentation to Measure the Heat Transfer Coefficients in an Automobile Radiator - Varma, Ramaraju Ramgopal; Abdullah, Ibrahim (Guru Nanak Publications, 2013)
The present investigation aims in development of an instrumentation to measure the heat transfer coefficients in an automobile radiator.